Konflik Batin Tokoh Utama Dalam Novel Warisan Karya Kembangmanggis: Kajian Psikologi Sastra - Chairunnisa, Ganis; Lubis, Haris Sutan; Marsella, Emma (Peneliti.net, 2024)
This research aims to describe the inner conflict experienced by the main character of the novel Pahlawan by Kembangmanggis using a literary psychology approach. This research uses Kurt Lewin's theory of approaching, moving away and approaching. The research method used in this research uses a qualitative descriptive method. The data presented is in the form of quotes, narratives, dialogues that contain conflict between the main characters. Data collection techniques start from reading novels and recording each data based on the theory used. The results of this research conclude that there is an inner conflict in the main character in the novel Pahlawan by Kembangmanggis which often occurs in the main character in the form of avoidance-avoidance conflict. This conflict appears more dominantly in the novel Pahlawan by Kembangmanggis.